ANALYSIS OF YIELD AND ITS COMPONENTS BASED ON HETEROSIS AND COMBINING ABILITY IN INDIAN MUSTARD (BRASSICA JUNCEA L. CZERN & COSS) - KUMAR, PARDEEP; LAMBA, ALANKAR; R. K. YADAV; SINGH , LOKENDRA; SINGH, MAHAK (The Bioscan, 2013)
A study of Diallel analysis excluding reciprocal cross, of seven parents was carried out to identify high heterotic crosses and their relationship in terms of general and specific combining ability (GCA and SCA) in Indian mustard in year 2010-11 and 2011-12 . Out of 21specific crosses, highest economic heterosis was observed in case of five crosses viz ; RK03-3 X RK03-4(43.90%), RK03-2 X RK03-4(34.55%), Varuna x RK03-4(31.75%), RH-819 X RH9801 (25.00%) and RH-819 X RK02-4(24.22%). ANOVA study of GCA and SCA variances for all the characters were significant except in case of secondary branches per plant. For all the character,ratio of GCA and SCA variances were below unity. Varuna and RK03-2 are the best parent for almost all traits as their GCA and per se performance are highest. Varuna X RK03-4 and Varuna X RK03-1showed high per se performance as well as SCA effects. The above best parent and best crosses can be used in hybridisation and heterosis breeding respectively.